The Staged Realism of Michael Haneke’s Caché - Niessen, Niels (Cinémas, 2009)
AbstractMichael Haneke’s style can best be described as staged realism, a cinematographic approach of presenting diegetic events as overtly staged and modelled in order to connect them to real social issues. In Caché (2005), this results in a short-circuit between the on-screen narrative and the viewer’s act of watching, as a result of which the viewer is created both as a guilty subject and as a co-investigator. Through a juxtaposition of Haneke’s staged realism with the neo-realist documentary mode of filmmaking advocated by André Bazin, this article argues that Caché is the current apex of Haneke’s realist project. However, by staging the real killing of animals, the film simultaneously troubles that project’s self-generated limits.